The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/anie.201711945
|View full text |Cite
|
Sign up to set email alerts
|

A Step Closer to Metal‐Free Dinitrogen Activation: A New Chapter in the Chemistry of Frustrated Lewis Pairs

Abstract: The end of the metal age: Recent developments in small-molecule activation and chemical transformations of main-group species pose the question as to whether metal catalysts could be avoided altogether in the activation of dinitrogen. A ground-breaking study by Stephan and co-workers clearly implies that the metal-free activation of N with frustrated Lewis pairs may be achievable in the not-too-distant future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 12 publications
0
64
0
3
Order By: Relevance
“…The NHC‐borane based FLP‐N 2 adducts 2.P2 and 4.P2 are significantly more stable (−55.0 and −61.7 kcal mol −1 ) than the corresponding NHC─N─N─borane adducts (−3.8 and 12.4 kcal mol −1 , respectively), and the latter can only lead to thermodynamically stable LA‐LB pair (Figure S7, Supporting Information). Similarly, previously isolable and thermodynamically favorable Lewis adduct Ph 2 C─N─N─B(C 6 F 5 ) 3 formed from diphenyldiazmehane and borane was proved to be highly unstable at ambient conditions to liberate N 2 molecule and a carbene‐borane adduct …”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The NHC‐borane based FLP‐N 2 adducts 2.P2 and 4.P2 are significantly more stable (−55.0 and −61.7 kcal mol −1 ) than the corresponding NHC─N─N─borane adducts (−3.8 and 12.4 kcal mol −1 , respectively), and the latter can only lead to thermodynamically stable LA‐LB pair (Figure S7, Supporting Information). Similarly, previously isolable and thermodynamically favorable Lewis adduct Ph 2 C─N─N─B(C 6 F 5 ) 3 formed from diphenyldiazmehane and borane was proved to be highly unstable at ambient conditions to liberate N 2 molecule and a carbene‐borane adduct …”
Section: Resultsmentioning
confidence: 93%
“…Interestingly, Stephan, Grimme, and co‐workers described the formation of thermodynamically favorable Lewis adduct Ph 2 C─N─N─B(C 6 F 5 ) 3 from diphenyldiazomethane and borane species, where N 2 is considered trapped in between a carbene Lewis base (LB) and borane Lewis acid (LA) . However, a combined experimental and theoretical study revealed this adduct was only stable at low temperature and it was highly sensitive to liberate N 2 molecule along with a carbene‐borane adduct at ambient temperature conditions . Recently, Hogler Braunschweig et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, the metal‐free N 2 activation by FLP still remains elusive . Caulton and co‐workers designed a series of reactions which were thermodynamically favorable for N 2 functionalization by theoretical calculations in 2013.…”
Section: Figurementioning
confidence: 99%
“…[34] However,t he metal-free N 2 activation by FLP still remains elusive. [41,42] Caulton and co-workers [43] designedaseries of reactions which were thermodynamically favorable for N 2 functionalization by theoretical calculations in 2013. However,a ll these studies weref ocused on the thermodynamicso fr eactions whereas the kinetics remains unclear.I tis well known that at hermodynamically favorable reaction will not occur if its kinetics is not favorable.…”
mentioning
confidence: 99%
“…Simonneau et al. classified the Group 6 metal analogues as transition‐metal frustrated Lewis pairs (TMFLPs)‐type activation of N 2 , and Tang et al . showed the first diazomethane‐B(C 6 F 5 ) 3 adduct, which features a bent B−N−N unit and is related to metal‐free FLP–N 2 capture (Figure d).…”
Section: Introductionmentioning
confidence: 91%